Analysis of the “Plan Fronteras” for Clean Cooking in Ecuador - MartÃnez-GÃ³mez, Javier; GuerrÃ³n, Gonzalo; Riofrio, A. J. (International Journal of Energy Economics and Policy, 2017)
The aim of this research is to analyze the introduction of the “Plan Fronteras” in Ecuador. The Plan Fronteras analyses the effects of introducing induction stoves in terms of electricity demand, energy consumption and greenhouse gas emissions, previous to the implementation of the National efficient cooking program, which is the first program of widespread access to clean cooking alternatives, which aims to introduce 3 million of induction stoves in the country. The impact of the induction stoves on Ecuador electric network has been analyzed by measuring electric grid parameters, energy and power consumption. The results of the study show that the electric grid parameters are within the permitted levels of the regulation of the country. Further on, a coincidence factor of 0.16 for induction stoves utilization has been registered when it was found. An estimation of the electric demand has been identified when implementing the National efficient cooking program with this value. The results of the study show that when analyzing the highlands and coastal regions at the same time, the peak demand in the country occurs at 19:00, whit a power requirement of 2860 MW. Finally, a study on energy demand and LPG savings after the implementation of the National efficient cooking program has been accomplished. The study has been evaluated and compared with future business as usual scenarios and new policies from 2016 until 2032. The results of the comparison reveal a reduction of the energy demand of 20 million GJ in 2032, and a reduction of 40.8 million tons of greenhouse gas emissions, between 2016 and 2032. Keywords: Household survey, clean cooking, acces to electricy, induction stoves, cooking fuel. JEL Classifications: L94, R52, Q4